Effect of embryo quality on pregnancy outcome in recipient cows and heifers - KARA, U.; ÇOBAN, S.; SAY, E.; HIZLI, H.; MUTLU, H.; NAK, Y.; SAĞIRKAYA, H.; AYAŞAN, T.; ÇOŞKUN, M.A.; ASARKAYA, A.; ERTEN, H.E.; YILMAZ, İ and YAZGAN, E. and ERDOĞAN, İ.E. and ERTEN, Z.M. and ERGÜL, Ş. and SERT, F. (Journal of the Hellenic Veterinary Medical Society, 2020)
This study was performed to compare the effects of embryo quality on pregnancy outcome in recipient cows and heifers. Embryos obtained from 83 Holstein donors were used in the study. In order to synchronize the recipients, 500 μg of cloprostenol were administered intramuscularly (i.m.), twice, at an interval of 11 days. In all recipients, one embryo was transferred to the upper 1/3 of the uterine horn ipsilateral to the ovary with the corpus luteum on the 7th day after oestrus onset (day 0). Each recipient received an i.m. injection of 5 μg of buserelin at the time ofembryo transfer. Pregnancy examinations were performed by ultrasonography on the day 30th post-transfer. A total of 345 (262 grade 1, 64 grade 2 and 19 grade 3) fresh embryos were transferred to 171 recipient cows and 174 recipient heifers. The pregnancy rates of the recipient cows and heifers were 41.52% and 52.29%, respectively (p<0.05).The pregnancy rates achieved with first, second and third quality grade embryos were 45.16%, 25.0% and 12.5% in the cows (p<0.05), and 55.11%, 41.66% and 54.54% in the heifers (p>0.05), respectively. In conclusion, the pregnancy rates was significantly higher in heifers than in cows (p<0.05) and, the embryo quality had a significant impact on recipient pregnancy outcome (p<0.05). The effect of embryo quality on pregnancy was significant in cows (p<0.05), but not significant in heifers (p>0.05).